(untitled) (Global Journal of Human-Social Science, 2018)
Violence against women has become a promine nt topic of discussion in India in recent years Politicians and media have placed great focus on the issue due to continuously increasing trends of violence against women Domestic violence also named as domestic abuse family violence is a pattern of behavior This involves violence or abuse by one person against another in a domestic setting According to a national family and health survey in 2005 total lifetime prevalence of domestic violence was 33 55 and 8 5 for sexual violence among women aged 15-49 65 of Indian men believe women should tolerate violence in order to keep the family together and women sometimes deserve to be beaten The instance of violence was reported to be lowest among Buddhist and jain women and highest among Muslim women in India Domestic violence can take place in number of forms including physical verbal emotional economic religious aspects Domestic violence murders including stoning bride burning Honor killings and dowry deaths Globally the victims of Domestic violence are overwhelmingly women and women tend to experience more severe forms of violence The Protection of women from Domestic Violence Act 2005 is an Act of parliament of India enacted to protect women from Domestic Violence The act of domestic violence towards women is a human rights violation as well as an illegal act under Indian law The Domestic Violence Act of 2005 has been used to prosecute domestic violence cases but activist s state that it discriminates against men The Delhi high court clarified that the Act could be used to prosecute women